Nanoscale melamine-based porous organic frameworks as host material for efficient polysulfides chemisorption in lithium–sulfur batteries. (1st December 2020) - Sun, Miao; Ji, Haifeng; Guan, Yani; Zhang, Yue; Zhang, Xiaojie; Jiang, Xiaoxia; Qu, Xiongwei; Li, Jingde
Abstract: In order to improve the electrochemical capacity of lithium–sulfur batteries (LiSBs), it is necessary to introduce the porous organic frameworks with well-defined hetero atom species in cathode. In this work, porous nanomaterials with ultra-high nitrogen containing and adjustable porosity named Schiff-based networks (SNWs) were selected as potential candidate for sulfur host in LiSBs. Two SNW samples have been constructed by reacting melamine with phenyl or biphenyl dialdehydes through microwave-assisted method, respectively. The high BET surface area provided sufficient room to impregnate sulfur and mitigated volume changes during the cycling performance. Besides, the high density and homogeneous distribution of pyridinic-N and aminic-N in SNW nanoparticles can cooperatively form lithium polysulfides (LiPSs) chemisorption via enhanced Li + –N interactions to effectively suppressed the 'shuttle effect'. Attributed to its structural superiorities, SNW/S cathode demonstrates excellent electrochemical performance in LiSBs. In particular, SNW-2/S cathode delivers an excellent cyclability with a specific capacity of 620 mAh · g −1 after 500 cycles at 0.5 C, counting with a low capacity fading of 0.0508% per cycle. This work highlights the importance of rational design for effective LiPSs chemisorption and pioneers a facile strategy for developing suitable sulfur host materials towards high-performance LiSBs.